FK506에 의한 Jurkat 세포자멸사 유전자 발현분석 - 장태영(Tae Young Jang); 이재숙(Jae Sook Lee); 우고운(Go Woon Woo); 김현철(Hyun Chul Kim); 이호균(Ho Kyun Lee); 정상영(Sang Young Chung) (Annals of surgical treatment and research, 2009)
Purpose: FK506 (tacrolimus) is a widely used immunosuppressive agent in the treatment of various medical conditions, including autoimmune disease, bone marrow and organ transplantations. Previously FK506 was known to cause apoptotic death of human Jurkat T cells. Methods: The current study was designed to analyze the gene expression pattern of Jurkat T cells after FK506 application by using cDNA microarray. Treatment of Jurkat T cells with FK506 resulted in a decrease of cell viability in a time- and dose-dependent manner. Next, total RNA of Jurkat T cells was extracted by using TRIzol reagent and used to carry out a confirmation test for the purity and integrity of total RNA. Results: Gene expression levels related to apoptosis and cell cycle process were mainly focused to analyze in FK506-treated Jurkat T cells. According to the inhibition of calcineurin activity, MARCKS in PKC substrates and Sp3 transcription factor was markedly increased in FK506-treated cells. Also, cell cycle control gene Id1 and Id3 were induced in expression from FK506-treated Jurkat T cells. However, FK506 decreased the expression of Src homology 2, G protein, and MEK 2 genes in bioactive peptide induced signaling pathway. It also reduced the expression level of the insulin receptor, DRPLA and Bai1-associated protein 2 genes, which are involved in the regulation of cell motility and morphology control. Conclusion: The author will continue to pursue the exact functional roles of genes that are markedly changed in expression by FK506 in human Jurkat T cells in vitro and in vivo experimental models. Purpose: FK506 (tacrolimus) is a widely used immunosuppressive agent in the treatment of various medical conditions, including autoimmune disease, bone marrow and organ transplantations. Previously FK506 was known to cause apoptotic death of human Jurkat T cells. Methods: The current study was designed to analyze the gene expression pattern of Jurkat T cells after FK506 application by using cDNA microarray. Treatment of Jurkat T cells with FK506 resulted in a decrease of cell viability in a time- and dose-dependent manner. Next, total RNA of Jurkat T cells was extracted by using TRIzol reagent and used to carry out a confirmation test for the purity and integrity of total RNA. Results: Gene expression levels related to apoptosis and cell cycle process were mainly focused to analyze in FK506-treated Jurkat T cells. According to the inhibition of calcineurin activity, MARCKS in PKC substrates and Sp3 transcription factor was markedly increased in FK506-treated cells. Also, cell cycle control gene Id1 and Id3 were induced in expression from FK506-treated Jurkat T cells. However, FK506 decreased the expression of Src homology 2, G protein, and MEK 2 genes in bioactive peptide induced signaling pathway. It also reduced the expression level of the insulin receptor, DRPLA and Bai1-associated protein 2 genes, which are involved in the regulation of cell motility and morphology control. Conclusion: The author will continue to pursue the exact functional roles of genes that are markedly changed in expression by FK506 in human Jurkat T cells in vitro and in vivo experimental models. KCI Citation Count: 0